Human resources and development in the Arabian Gulf (The Emirates Center for Strategic Studies and Research, 2010)
The six member states of the Gulf Cooperation Council (GCC) have in recent decades experienced substantial and rapid development progress, as evidence by their high rankings in the United Nation's Development Programme's Human Development Index (HDI). But despite these achievements, the process of development in the GCC still faces numerous challenges, the most significant of which relate to national human resources. This volume therefore offers an extensive examination of the different development strategies available to the GCC states in the face of the challenges of human resource development, the problems facing GCC labour markets, the opportunities and potential for investment in human capital and the many obstacles to sustainable development in the Gulf. This book will be an essential resource for those involved in the most important issues and debates for the future of human resources and development in the Gulf, the Middle East and wider developing world. -- Product Description